Exploring the Heublein model to resolve postgraduate student dropout in a Malaysian public university / Yuen Fook Chan ... [et al.] - Yuen, Fook Chan; Supramanian, Kaarthiyainy; Hassan, Zainudin; Mohd Yusof, Sanitah (Universiti Teknologi MARA, 2024)
‘University dropout’ is a term widely used to describe a phenomenon where students who have enrolled at a university decides to quit the programme before completing it. This could occur at any level such as a course/subject of study, a department, a faculty, a university, or the entire system of higher education. Students quit their studies due to a combination of factors. Theoretical work and empirical findings have already conceptualized numerous factors to the dropout issue, but little is known about the interplay of these factors especially those relating to the Heublein model. Hence, this qualitative study investigated PhD students’ dropout issue based on the model in a public university in Malaysia. The study obtained data from eight postgraduate students who quit their PhD programmes at a public university in Malaysia. The informants identified reasons relating to financial situation, counselling services, living condition, and their future plans. Most left at semester three after failing their defence of research proposal. A detailed analysis also revealed that eight PhD candidates also faced various socio-economic reasons at the time of their dropout. These factors corresponded to academic performance and socio-economic-factors, academic self-concept, and the intention to dropout. Such profiles identified in this study should be taken into consideration for targeted interventions in universities for dropout students.